Liquid crystal modulator in the channel of a laser projection microscope - Oleksenko, P.; Sorokin, V.; Zelinskyy, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Using the light modulator based on electrically controlled reflection in the interface between isotropic dielectric and nematic liquid crystal has been viewed. The optical scheme of a laser projection microscope (LPM) with a liquid crystal modulator (LCM) in treatment, observation and recording channels has been proposed, implemented and investigated. In the proposed scheme, LCM can act as a light beam splitter, attenuator and modulator simultaneously. Possibilities of some thin film materials processing by LPM with LCM in the treatment, observation and recording channels are demonstrated.